Random thoughts on the subject of artificial intelligence and health data (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The text examines the use of health data combined with modern artificial intelligence systems. The aim is to provide a brief and introductory treatment of the subject. In particular, it addresses several current issues with implications for constitutionally guaranteed rights. the legal bases for the processing of personal data in the context of clinical trials, consent as the legal basis for the primary and secondary use of personal data. The processing of digitised health data. Duties and obligations to provide information in healthcare.
Keywords: Health data; artificial intelligence; fundamental rights; European Health Data Space